ANALYSIS OF STUDENTS’ MATHEMATICAL COMMUNICATION SKILLS BASED ON GENDER IN SOLVING SOCIAL ARITHMETIC PROBLEMS - Azela Fitri; Darhim Darhim (FKIP Universitas Muhammadiyah Tangerang, 2023)
Students must master mathematical abilities, one of which is mathematical communication skills. The purpose of this study is to describe how the description of students' mathematical communication skills based on gender differences in solving social arithmetic problems. The subjects of this studi were three female students and three male students who had studied social arithmetic in class. The method used in this research is qualitative method. The research was conducted at SMPN 35 Bandung. Qualitative methods are used in this research. The results of this study are that gender differences in solving social arithmetic problems can affect students' mathematical communication abilities. Female students as a whole have a greater percentage of scores on all indicators of mathematical communication skills than male students.